2009
DOI: 10.1002/cvde.200806737
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Scale Synthesis of Few‐Layered Graphene using CVD

Abstract: Large-scale, substrate-free graphene, with few-layered sheets, is synthesized by the CVD of methane over cobalt supported on magnesium oxides at 1000 -C in a gas flow of argon. Typically, 50 mg of the few-layered graphene materials over 500 mg of the Co/MgO catalysts are synthesized under our experimental conditions. Randomly aggregated, thin, crumpled graphene sheets stacked closely together are produced. Both carbon (94.6 at.-%) and oxygen (5.4 at.-%) are present in the graphene sheets. The oxygen may origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
87
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(95 citation statements)
references
References 27 publications
0
87
0
2
Order By: Relevance
“…Graphene can generally be produced through two different techniques such as top-down and bottom-up. The bottom-up method is including Epitaxial growth technique [68], chemical vapor deposition (CVD) [69] and unzipping of carbon nanotubes [70] while; graphite exfoliation is considered as the top-down approach [71].…”
Section: Reinforcementmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene can generally be produced through two different techniques such as top-down and bottom-up. The bottom-up method is including Epitaxial growth technique [68], chemical vapor deposition (CVD) [69] and unzipping of carbon nanotubes [70] while; graphite exfoliation is considered as the top-down approach [71].…”
Section: Reinforcementmentioning
confidence: 99%
“…Graphene can generally be produced through two different techniques such as top-down and bottom-up. The bottom-up method is including Epitaxial growth technique [68], chemical vapor deposition (CVD) [69] and unzipping of carbon nanotubes [70] while; graphite exfoliation is considered as the top-down approach [71]. Graphene have considered as an interesting materials which could be used in several applications owing to its noticeable properties such as elastic modulus (1 TPa), the strength (130 GPa), the thermal and the electrical conductivity (5300 W/m·K and 6000 S/cm, respectively) and ultra-high surface area [67].…”
Section: Reinforcementmentioning
confidence: 99%
“…Different substrates, including platinum (Pt) [59], iridium (Ir) [60] and germanium (Ge) [61,62] have also been mentioned. It was first reported that the graphene deposited on the Co/MgO substrate has better application prospects for molecular electronics and polymer composites [63]. To reduce energy consumption and deposit graphene directly on the electronic device, using low temperature to synthesize graphene has become a research hot spot.…”
Section: Conventional Chemical Vapor Deposition Growth On Cumentioning
confidence: 99%
“…A typical system is illustrated in Figure 10. Graphene synthesis by this method has been reported from around 2008 [8][9][10][11][12][13][14][15][16][17][18][19][20][21], that is, about four years after the discovery of single layer graphene by physical exfoliation. Table 1 summarizes some of the conditions for obtaining single to few layer graphene on various substrates employing the stipulated catalysts in each case.…”
Section: Chemical Vapour Depositionmentioning
confidence: 99%